Numerical study of the adaptation of directional solidification furnaces for the production of monolike Ingots - Oubbati, Fadia; Nouri, Abdallah (Université Amar Telidji - Laghouat - Département des sciences de la matière, 2020)
Reducing the energy consumption in the Silicon and Sapphire industry is related to the development of new processes and materials, as part of this study, we described the techniques used in the production of Silicon and Sapphire ingots as well as the influence of their control parameters, such as the temperature distribution in the directional solidification furnaces. We used a numerical simulation; improvements were made based on the furnaces standard design. The results were very interesting; they give the possibility of producing mono-like ingots of Silicon and Sapphire using multi crystalline techniques with controlling the thermal configuration of the furnace. These improvements can help the Silicon and Sapphire producers for increasing the productivity and reducing the energy consumption and costs.